The Advantages of Hiring Persons with Moderate Disabilities on the Profitability of Food Enterprises in Metro Manila - Dait, Amorei V (Animo Repository, 2023)
In a world that values diversity and inclusivity, the visibility of persons with disabilities (PWDs), particularly in the workforce, is pivotal in social progress. However, misconceptions often hinder their employment issues, leading to underrepresentation in various industries. Given such, this study highlights the advantages of hiring moderately disabled individuals in the food sector of Metro Manila, specifically emphasizing on employee performance, human resource diversity, and customer perceptions, and how they affect profitability. As a qualitative research, structured interviews were conducted with employees from select food enterprises. These are Caravan Food Group Incorporated and Farron Cafe. The results reveal the advantages of inclusivity in heightened job applications, employee competency by PWDs and able-bodied colleagues, positive customer perceptions and productive engagements. Most notably, it is through positive customer engagements that result in voluntary and incidental marketing that contributes to potential revenue growth. Simultaneously from an advocacy perspective, this study challenges stereotypes and encourages businesses to recognize the untapped potential of moderately disabled individuals. By providing diverse avenues, companies are creating an inclusive society that benefits from disabled individuals’ valuable contributions.